Contractile efficiency of dystrophic mdx mouse muscle: in vivo and ex vivo assessment of adaptation to exercise of functional end points - Roberta Francesca Capogrosso; Paola Mantuano; Anna Cozzoli; Francesca Sanarica; Ada Maria Massari; Elena Conte; Adriano Fonzino; Arcangela Giustino; Jean‐François Rolland; Angelo Quaranta; Michela De Bellis; Giulia Maria Camerino; et al. (2017)
Progressive weakness is a typical feature of Duchenne muscular dystrophy (DMD) patients and is exacerbated in the benign mdx mouse model by in vivo treadmill exercise. We hypothesized a different threshold for functional adaptation of mdx muscles in response to the duration of the exercise protocol. In vivo weakness was confirmed by grip strength after 4, 8, and 12 wk of exercise in mdx mice. Torque measurements revealed that exercise-related weakness in mdx mice correlated with the duration of the protocol, while wild-type (WT) mice were stronger. Twitch and tetanic forces of isolated diaphragm and extensor digitorum longus (EDL) muscles were lower in mdx compared with WT mice. In mdx, both muscle types exhibited greater weakness after a single exercise bout, but only in EDL after a long exercise protocol. As opposite to WT muscles, mdx EDL ones did not show any exercise-induced adaptations against eccentric contraction force drop. qRT-PCR analysis confirmed the maladaptation of genes involved in metabolic and structural remodeling, while damage-related genes remained significantly upregulated and angiogenesis impaired. Phosphorylated AMP kinase level increased only in exercised WT muscle. The severe histopathology and the high levels of muscular TGF-β1 and of plasma matrix metalloproteinase-9 confirmed the persistence of muscle damage in mdx mice. Therefore, dystrophic muscles showed a partial degree of functional adaptation to chronic exercise, although not sufficient to overcome weakness nor signs of damage. The improved understanding of the complex mechanisms underlying maladaptation of dystrophic muscle paves the way to a better managment of DMD patients. NEW & NOTEWORTHY We focused on the adaptation/maladaptation of dystrophic mdx mouse muscles to a standard protocol of exercise to provide guidance in the development of more effective drug and physical therapies in Duchenne muscular dystrophy. The mdx muscles showed a modest functional adaptation to chronic exercise, but it was not sufficient to overcome the progressive in vivo weakness, nor to counter signs of muscle damage. Therefore, a complex involvement of multiple systems underlies the maladaptive response of dystrophic muscle.